Custom in Islamic Law and Legal Theory - Shabana, Ayman. author. aut Link
XV, 246 p.
Keywords: This book explores the relationship between custom and Islamic law and seeks to uncover the role of custom in the construction of legal rulings. On a deeper level, however, it deals with the perennial problem of change and continuity in the Islamic legal tradition (or any tradition for that matter).